Response to antibiotics of women with symptoms of urinary tract infection but negative dipstick urine test results: double blind randomised controlled trial. Issue 7509 (22nd June 2005) - Richards, Dee; Toop, Les; Chambers, Stephen; Fletcher, Lynn
Abstract: Objective To assess the effectiveness of antibiotic treatment of women with symptoms of urinary tract infection but negative urine dipstick testing. Design Prospective, double blind, randomised, placebo controlled trial. Setting Primary care, among a randomly selected group of general practitioners in Christchurch, New Zealand. Participants 59 women aged 16-50 years presenting with a history of dysuria and frequency in whom a dipstick test of midstream urine was negative for both nitrites and leucocytes. Participants with complicated urinary tract infection were excluded. Intervention Trimethoprim 300 mg daily for three days or placebo. Main outcome measures Self reported diary of symptoms for seven days, recording the presence or absence of individual symptoms each day, followed by a structured telephone questionnaire after seven days. The main clinical outcome was resolution of dysuria at three and seven days and median time to resolution. Secondary outcomes were resolution of other symptoms. Results The median time for resolution of dysuria was three days for trimethoprim compared with five days for placebo (P = 0.002). At day 3, five (24%) of patients in the treatment group had ongoing dysuria compared with 20 (74%) in the placebo group (P = 0.005). This difference persisted until day 7: two patients (10%) in the treatment group v 11 (41%) in the placebo group; P = 0.02). The number needed to treat was 4. The median duration of constitutional symptoms (feverishness, shivers) was reduced by four days. Conclusions Although a negative dipstick test for leucocytes and nitrites accurately predicted absence of infection when standard microbiological definitions were used (negative predictive value 92%), it did not predict response to antibiotic treatment. Three days' treatment with trimethoprim significantly reduced dysuria in women whose urine dipstick test was negative. These results support the practice of empirical antibiotic use guided by symptoms. Balancing the competing interests of symptom relief and the minimisation of antibiotic use remains a dilemma—further research is needed to determine clinical predictors of response to antibiotics.